Review on bio-based plastic for future applications - Abu Bakar, Nurul Fathihah; Othman, Siti Amira
This paper reviews the future applications of bio-based plastics. Most plastics are made through petrochemical processes. In other words, they start out as the chemical byproducts of oil refining, which are turned into a variety of plastics through chemical processes that form long molecular chains known as polymers. These polymers give plastics their structure. Bioplastics are biodegradable materials that come from renewable sources and can be used to reduce the problem of plastic waste that is suffocating the planet and contaminating the environment. The advantages of using bioplastics are bioplastics won’t leach chemicals into food, non- toxic and offer a zero waste end life options. Bioplastics can be recycled with conventional plastics to produce a great material for food packaging. It also has a socioeconomic benefit that often have a positive impact on the consumers who are increasingly becoming aware of environmental issues. As conclusion, it is proven that bioplastics give promising future to cleaner and safer world.